2016
DOI: 10.1007/s12011-016-0651-1
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Deficiency-Induced Inflammation and Increased Expression of Regulating Inflammatory Cytokines in the Chicken Gastrointestinal Tract

Abstract: Selenium (Se), a nutritionally essential trace element, plays an important role in various aspects of health for a wide range of species, including birds. Se deficiency inhibits the growth of immune organs and decreases immune function, leading to many inflammatory diseases. The present study determined the effects and mechanism of dietary Se deficiency on gastrointestinal tract tissue inflammation. The histopathological changes showed that Se deficiency induced inflammatory lesions in the gastrointestinal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Studies have reported that selenium may inhibit the activation of NF-κB ( Duntas, 2009 ; Liu et al., 2016 ), and the intake of a low-selenium diet was often accompanied by the increase of IL-6 , IL-1β , and TNF-α ( Tsuji et al., 2015 ; Zhou et al., 2014 ), thus aggravating gastrointestinal inflammatory lesions ( Gao et al., 2016 ; Liu et al., 2016 ). In this study, a marked reduction in the expression of TLR4 in the intestine of juvenile grass carp supplied with HFD containing nano-Se, followed by a significant decrease in the expression of p38 MAPK and NF-κB p65 was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that selenium may inhibit the activation of NF-κB ( Duntas, 2009 ; Liu et al., 2016 ), and the intake of a low-selenium diet was often accompanied by the increase of IL-6 , IL-1β , and TNF-α ( Tsuji et al., 2015 ; Zhou et al., 2014 ), thus aggravating gastrointestinal inflammatory lesions ( Gao et al., 2016 ; Liu et al., 2016 ). In this study, a marked reduction in the expression of TLR4 in the intestine of juvenile grass carp supplied with HFD containing nano-Se, followed by a significant decrease in the expression of p38 MAPK and NF-κB p65 was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of organic Se in the broiler diet include increased Se transfer to the muscles and the build-up of Se reserves in the body, which is expected to result in improved chicken resistance to various stresses and to have a positive effect on immunity, gut health, and meat quality (Surai, 2006;Fisinin et al, 2008;Surai and Fisinin, 2014). In particular, it has been recently shown that Se deficiency in chickens promotes gut inflammation (Gao et al, 2016;Wu et al, 2016). Furthermore, specific emphasis has been placed on protein oxidation in relation to meat quality, including water-holding capacity of meat and drip loss.…”
Section: Organic Se Concept Developmentmentioning
confidence: 99%
“…Selenium (Se) is an essential trace element [ 1 , 2 ] that evinces antioxidant activity [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], anti-inflammatory [ 2 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], antimutagenic [ 26 , 27 ], anticarcinogenic [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] or chemopreventive [ 2 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], antiviral [ 2 ], antibacterial [ 45 , 46 , 47 , 48 ], antifungal [ 49 , 50 ] and antiparasitic effects [ 51 ,…”
Section: Biochemistry Of Seleniummentioning
confidence: 99%